STUDY OF USE FERMENTED BANANA Musa paradisiaca (Linnaeus, 1761) HUMPS AS ORGANIC FERTILIZER TO IMPROVE NATURAL FEED AVAILABILITY IN NURSERY OF HOVEN’S CARP Leptobarbus hoevenii (Bleeker, 1851) FRY - Wahid Abdul Rosyid; Indra Gumay Yudha; Herman Yulianto (University of Lampung, 2019)
Plankton as a natural feed is thought to be a factor that affects the growth of hoven’s carp fry. Plankton abundance can be increased by the addition of organic fertilizers containing nutrients (nitrate and phosphate). Nutrients abundance can be increased by addition of fermented banana hump’s This research aimed to determine the use of fermented banana’s hump to increase the availability of natural feed nursery and the growth of hoven’s carp fry. The method of this research used a completely randomized design with four treatments and three replications, i.e: P1 (control), P2 (5,0 ppm), P3 (7,5 ppm), and P4 (10,0 ppm) addition of fermented banana’s hump. The measured parameters were nitrate, phosphate, plankton abundance, growth and water quality. The results showed the dose of addition of banana weed fertilizer had an effect (P< 0.05) on the abundance of natural feed and the growth of hoven’s carp fry. Results of water quality measurement showed the parameters of temperature ranged from 25 to 27 °C, pH ranged from 6,23 to 7,53, DO ranged from 3,40 to 11,36 and ammonia from 0 to 0,001 mg/l. The recomended dosage of fermented banana’s hump was 10 ppm for 1 l of water media.